Gerakan Masyarakat Dalam Isu Lingkungan : Studi Pada Gerakan Greenpeace Sebagai Gerakan Enviromentalism - Muhamad Fathan Mandela (Journal of Politics and Democracy, 2026)
Abstract. This article will examine how Greenpeace Indonesia continues to organize community movements related to environmental issues. As an organization, Greenpeace ultimately carries out movements with members from the wider community and often vis-à-vis with many countries and companies for their environmental campaigns. This article uses the framework of environmentalism to examine the movements carried out by Greenpeace. Meanwhile, this article uses a qualitative method with a descriptive approach. The results in this article show that Greenpeace's actions and campaigns are motivated by injustice, how Greenpeace confronts several companies that cause environmental damage, which means endangering human life in the future.